2017
DOI: 10.5860/crl.77.6.16557
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Service Innovation in Academic Libraries through the Lens of Disruptive Innovation

Abstract: With the development of digital technologies, various disruptive innovations have emerged that are gradually replacing academic libraries in the information-seeking process. As academic libraries become less relevant to their users, it is imperative that they develop strategies to respond to disruption. We highlight the fact that the service mission of academic libraries is in alignment with service innovation and propose that academic libraries respond to disruption by accelerating service innovation. Applyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 15 publications
(15 reference statements)
0
12
0
1
Order By: Relevance
“…For example, Yeh and Walter (2016) examine the determinants of service innovation in academic libraries.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Yeh and Walter (2016) examine the determinants of service innovation in academic libraries.…”
Section: Resultsmentioning
confidence: 99%
“… Patillo et al (2009) also found academic librarians have more autonomy than public librarians and librarians with administrative or information technology roles experience higher levels of autonomy. Yeh and Walter (2016) proposed that the autonomy of librarians and library committees is a crucial factor towards creating innovative solutions to combat the evolving demands placed on academic libraries. Work autonomy's relationship to constructs such as job satisfaction, motivation, commitment, and decreases in stress, point to work autonomy as an important tool for academic library managers to deploy towards increasing performance and potentially workplace morale.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…The competitors have increased over the years because of information brokerage, globalisation as well as the evolution of information technologies and networks (Patkar, 2010). Most of them have aggressive, fast-paced and disruptive approaches, offering advanced and improved services and products (Esse, 2013; Pinfield et al , 2017; Yeh and Walter, 2017). Similarly, they are more equipped with sophisticated technology, current library resources and adequate funding that enhance their ability to provide much-needed information to the information seekers, thus making it difficult for academic libraries to contend (Esse, 2013; Farney and McHale, 2013).…”
Section: Drivers Of CImentioning
confidence: 99%
“…Given the increasing need and pressure for efficiency, productivity and competitiveness in academic libraries, the need to explore and intensify the adoption of Internet technologies as competitive and innovative tools has heightened (Appleton et al , 2011; Al Hijji, 2012; Tait et al , 2016; Pietruch-Reizes, 2010; Uzohue and Yaya, 2016; Pinfield et al , 2017; Yeh and Walter, 2017). Although the adoption of technologies is touted as the solution, there is evidence that it could be impacted negatively by challenges such as the following: slow adoption of technology, budgetary constraints, lack of leadership and inadequate skills level.…”
Section: Drivers Of CImentioning
confidence: 99%